Short Selling Around Seasoned Equity Offerings - Henry, Tyler R.; Koski, Jennifer L. (Review of Financial Studies, 2010)
We use daily short-selling data to examine whether short selling around seasoned equity offerings (SEOs) reflects informed or manipulative trading. Around SEO announcements, we find no evidence of informed short selling. Around issue dates, higher levels of pre-issue short selling are significantly related to larger issue discounts for non-shelf-registered offerings. This evidence is consistent with manipulative trading. We show that SEC Rule 105 constrains some but not all manipulative trading. Our results reverse previous research that uses monthly short-interest data, because daily data allow more powerful tests. Our evidence helps explain the increased popularity of shelf registrations. Although short selling usually enhances price efficiency, we document a situation where short selling reduces price efficiency.